Determinan CSR dan Dampaknya Terhadap Nilai Perusahaan: (Studi Empiris Pada Perusahaan Pertambangan Terdaftar di BEI) - Kiki Yuliandara; Amri Amrulloh; Amir Indrabudiman; Sugeng Riyadi (Jurnal Akuntansi Bisnis dan Ekonomi, 2019)
This study aims to analyze the effect of Good Corporate Governance, Leverage and Company Size on Corporate Social Responsibility and its impact on Corporate Value. The data in this study were obtained through the website www.idx.co.id and web.idx.id, to obtain the annual financial statements of companies that have gone public in Indonesia. The purposive sampling method is used in determining sample selection. As many as 26 of the 45 Mining Sector companies listed on the Indonesia Stock Exchange with 5 years of observations, starting from 2013 to 2017, obtained 130 research samples. The statistical method used to test the hypothesis is Partial Least Square. The results of this study found that Good Corporate Governance has no significant effect on Corporate Social Responsibility, Leverage has a significant negative effect on Corporate Social Responsibility, Company Size has a significant positive effect on Corporate Social Responsibility, Good Corporate Governance has a significant positive effect on Corporate Value, Leverage does not significantly influence Company Value, Company Size has no significant negative effect on Corporate Values ??and Corporate Social Responsibility has a significant negative effect on Corporate Values, and Corporate Social Responsibility Able to mediate the influence of Good Corporate Governance, Leverage and Company Size on Firm Value.